Pemanfaatan Mesin Pencetak Pellet Portabel Untuk Membuat Pakan Ikan Berbahan Baku Yang Mudah dan Murah - Sukardi Sukardi; Muhammad Hudan Rahmat; Syarpin Syarpin; Adit Setiawan; Hanifa Risqiana (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The high price of raw materials for making fish feed (pellets) has an impact on the decreasing productivity of partner fish farming. There needs to be an alternative innovation that is easy and cheap. The purpose of PkM is to provide (1) information to partners about Maggots as raw materials for pellets, (2) knowledge and skills to partners on how to make pellets using a portable printing machine using easy and cheap raw materials, and (3) assistance to partners on catfish farming in drums. The stages of the activity include Preparation, Machine Making, Implementation, Evaluation and Reporting. The success of the program is seen from the increase between the pre-test and post-test. Data analysis uses the t-test, assisted by SPSS. The results of PkM concluded that there was a significant difference between the pre-test and post-test scores in (1) knowledge about Maggots as raw materials for pellets, and (2) knowledge and skills in making pellets. The significance of each variable is less than 0.05 (sig. <0.05). The n-gain value of each variable is 0.73 and 0.83 in the high category.